2011
DOI: 10.1080/10382046.2011.619811
|View full text |Cite
|
Sign up to set email alerts
|

Student-teachers’ use ofGoogle Earthin problem-based geology learning

Abstract: Geographical Information Systems (GIS) are adequate for analyzing complex scientific and spatial phenomena in geography education. Google Earth is a geographic information tool for GIS-based learning. It allows students to engage in the lesson, explore the Earth, explain what they identify and evaluate the implications of what they are learning. This paper introduces one example of using Google Earth for problem-based learning processes in teacher education. Student-teachers' geographical thinking was analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 28 publications
(33 reference statements)
0
12
0
6
Order By: Relevance
“…By creating activities closely associated with real-world problems and issues, PBL and related methods (i.e., inquirybased learning) have been shown to promote higher-order learning and critical thinking skills within both GIS&T and geography (Aangeenbrug, 1992;Chen, 1998;Wilder, Brinkerhoff, & Higgins, 2003;Drennon, 2005;Reed, 2010;Howarth & Sinton, 2011;Oyana, 2012;Shulz, 2012;Weiss, 2017). Other fields that have benefitted from these methods include environmental education (Ratinen & Keinonen, 2011), science (van Joolingen, de Jong, & Dimitrakopoulou, 2007, geology (Apedoe, Walker, & Reeves, 2018), physics (Sorensen, McBride, & Rebello, 2011), chemistry (Nedungadi, Malini, & Raman, 2015), and biology (Carrió et al, 2016). One successful example of using PBL in GIS&T instruction is illustrated by field-based exercises, where data captured using Global Navigation Satellite System (GNSS) receivers (e.g., GPS, GLONASS) are integrated within GIS (Carlson, 2007;Miller et al, 2007;Favier & van der Schee, 2009).…”
Section: Gisandt Pedagogiesmentioning
confidence: 99%
“…By creating activities closely associated with real-world problems and issues, PBL and related methods (i.e., inquirybased learning) have been shown to promote higher-order learning and critical thinking skills within both GIS&T and geography (Aangeenbrug, 1992;Chen, 1998;Wilder, Brinkerhoff, & Higgins, 2003;Drennon, 2005;Reed, 2010;Howarth & Sinton, 2011;Oyana, 2012;Shulz, 2012;Weiss, 2017). Other fields that have benefitted from these methods include environmental education (Ratinen & Keinonen, 2011), science (van Joolingen, de Jong, & Dimitrakopoulou, 2007, geology (Apedoe, Walker, & Reeves, 2018), physics (Sorensen, McBride, & Rebello, 2011), chemistry (Nedungadi, Malini, & Raman, 2015), and biology (Carrió et al, 2016). One successful example of using PBL in GIS&T instruction is illustrated by field-based exercises, where data captured using Global Navigation Satellite System (GNSS) receivers (e.g., GPS, GLONASS) are integrated within GIS (Carlson, 2007;Miller et al, 2007;Favier & van der Schee, 2009).…”
Section: Gisandt Pedagogiesmentioning
confidence: 99%
“…Genomgångna studier påvisar att GIS öppnar upp för geografiundervisning, både i lärarutbildningen och skolundervisningen, som baseras på aktivt, forskningsbaserat, kooperativt och problembaserat lärande, och som främjar lärande om komplexa ämnesövergripande problemområden (Andersland, 2011;Favier & van der Schee, 2012;Hauselt & Helzer, 2012;Patterson, 2007;Ratinen & Keinonen, 2011). Detta skulle kunna förändra skolans undervisning från att fokusera på namngeografi till att bli mer problemorienterad (Molin, 2006;Molin och Örbring, 2017) och på detta sätt öka elevers möjligheter att uppnå de förmågor som styrdokumenten föreskriver (Carlgren 2011;Svanelid, 2014).…”
Section: Undervisning För Att Främja Studenters Och Elevers Lärandeunclassified
“…Detta skulle kunna förändra skolans undervisning från att fokusera på namngeografi till att bli mer problemorienterad (Molin, 2006;Molin och Örbring, 2017) och på detta sätt öka elevers möjligheter att uppnå de förmågor som styrdokumenten föreskriver (Carlgren 2011;Svanelid, 2014). Detta förutsätter dock ett stort engagemang hos lärarutbildare och skollärare vad gäller utveckling av undervisningsmaterial och handledning av projekt (Andersland, 2011;Ratinen & Keinonen, 2011). Lärares förmågor att skapa ett öppet klimat och föra en dialog med studenter och elever samt att ge formativ feedback är avgörande för positiva resultat (Biggs & Tang, 2007;Favier & van der Schee, 2012).…”
Section: Undervisning För Att Främja Studenters Och Elevers Lärandeunclassified
See 1 more Smart Citation
“…Through virtual field trips, students can interact with remote, inaccessible or potentially hazardous areas (e.g., volcanic lava flows) through participation, exploration, analysis and the learning and the testing of skills at any time due to the removed barriers of space, time and geographical location (Litherland & Stott, 2012;Tuthill & Klemm, 2002). Ratinen and Keinonen (2011) suggested that field trips done with Google Earth facilitate students' spatial thinking and critical analytical skills. Ratinen and Keinonen (2011) suggested that field trips done with Google Earth facilitate students' spatial thinking and critical analytical skills.…”
Section: Authentic Outdoor Learning Experiences or Virtual Fieldworkmentioning
confidence: 99%